Erregerspektrum postoperativer Komplikationen in der Viszeralchirurgie: das Problem der Multiresistenz = Spectrum of pathogens in postoperative complications of visceral surgery : the problem of multidrug resistance - Kramer, Axel; Harnoß, Julian-Camill (Der Chirurg, 2017)
In general surgery the etiology of surgical site infections has not significantly changed over the last 30 years. Gram-positive bacteria, e.g. coagulase negative staphylococci (CNS), Staphylococcus aureus and Enterococcus spp. as well as Gram-negative bacteria, e.g. Escherichia coli, Enterobacter spp., Klebsiella spp. and Pseudomonas aeruginosa, are the most common findings. Although in general surgery 10% of the S. aureus causing postoperative wound infections were methicillin resistant (MRSA), no cases of multidrug-resistant Gram-negative (MRGN) bacteria were reported. Yeasts (particularly Candida spp.) are rarely the pathogen causing surgical site infections (≤3%) and concomitant risk factors are typical (e.g. diabetes, chemotherapy, immunosuppression and malnutrition). Viruses are rarely the cause of surgical site infections. Transmission can occur by HBV, HCV or HIV positive surgical staff or in organ transplantations and postoperative reactivation of persistent infections is possible (especially for HBV, HCV, CMV, EBV and HIV). The principles for prevention of surgical site infections are dealt with as consequences of preoperative colonization by MRSA, methicillin-sensitive S. aureus (MSSA) and MRGN and reviewed with respect to screening, perioperative antibiotic prophylaxis and decolonization. In nosocomial peritonitis, the selection of antibiotics should consider previous antibiotic treatment. A single intra-abdominal detection of Candida spp. usually does not require antimycotic treatment in postoperatively stable and immunocompetent patients but is recommended in severe community-acquired or nosocomial peritonitis. Viral infections can be avoided by screening of organ donors and serological surveillance of surgery personnel.
Gesehen am 12.11.2018